Evaluation that counts: A review of climate change adaptation indicators & metrics using lessons from effective evaluation and science-practice interaction. Issue 66 (December 2016) - Arnott, James C.; Moser, Susanne C.; Goodrich, Kristen A.
Highlights: Indicators & metrics (I&M) for climate change adaptation are found across geographic scales, sectors, and spheres of practice. I&M address diverse evaluation functions and are developed using a wide range of collaborative practices. I&M development may be seen as a site of science-practice interaction and as an opportunity for building adaptive capacity. Employing emerging best practices in evaluation and science-practice interaction could increase I&M usefulness for climate adaptation. Abstract: Amid growing effort to move towards implementation of climate change adaptation, serious interest is emerging about how to use indicators and metrics (I&M) to evaluate adaptation success. Cities are among the leading experimenters developing I&M, but many other entities also view I&M as a tool for providing clarity and accountability about the goals and progress of adaptation. The current landscape of this work is scattered: I&M examples, frameworks, and guidance documents reflect motivations, contexts, and approaches as diverse as the field of adaptation itself. This study systematically surveys the "growth industry" of I&M, including a special focus on I&M approaches developed for cities anywhere and by US cities in particular. We classify these I&M efforts into four domains: those developed in academia, by program sponsors, boundary organizations, and on-the-ground implementers. With attention to theory on (program) evaluation and on science-practice interaction, we reveal a broad range of I&M evaluation purposes and collaboration practices. We conclude that evaluation of adaptation progress and effectiveness – if it is to usefully inform the work of cities or other implementers – would benefit from greater attention to the best practices and guidance offered in the related, but largely still separate, fields of evaluation and science-practice interaction.